Laboratory Predictors of Mortality in Patients with Heart Failure and Reduced Left Ventricular Ejection Fraction - Mariia V. Kucheriava; Georgii B. Mankovskyi (Ukrainian Journal of Cardiovascular Surgery, 2023)
Introduction. Heart failure (HF) is a growing epidemic with high morbidity and mortality rates. In general, mortality in patients with HF is 10.4% after 30 days from admission, 22% after 1 year, and 42.3% after 5 years, despite the introduction of new evidence-based drug therapy and advance in surgical interventions. There is a range of predictors/ factors that need to be addressed to reduce the risk of mortality and to assess prognosis in patients with heart failure and reduced left ventricular ejection fraction.The aim. To determine the laboratory factors predicting 2-year mortality in patients with coronary artery disease and heart failure and reduced left ventricular ejection fraction after percutaneous coronary intervention (PCI) by analysis of basic patient data.Materials and methods. This one-center analysis, conducted at the Ukrainian Children’s Cardiac Center, Clinic for Adults, included 178 patients who had chronic stable coronary artery disease with heart failure and reduced left ventricular ejection fraction, who underwent PCI in the period between January 2020 and January 2022. The endpoint of our study was all-cause mortality. The studied group of patients was divided into two subgroups: S (“survival”) with patients who survived during the observation period after PCI, and D (“death”) including patients who died before the end of this observation period after the PCI. A p-value of less than 0.05 was considered statistically significant.Results. The mean length of hospital stay was 3 (1-5) days. Total bilirubin, total cholesterol, sodium, N-terminal pro B-type natriuretic peptide (NT-proBNP) level, hemoglobin, albumin and lymphocytes were significantly different in the two subgroups. In the multivariate model, the strongest independent predictors of patient mortality were: elevated NT-proBNP (adjusted hazard ratio [HR] for one standard deviation 1.44, 95% confidence interval [CI] 1.32 to 1.57, p<0.0001), low albumin (HR 1.64, 95% CI 1.10 to 2.23, p=0.008), hyponatremia (HR 1.69, 95% CI 1.16 to 2.22, p<0.001), lymphopenia (HR 1.54, 95% CI 1.10 to 2.20, р<0.001, decreased hemoglobin level (HR 1.25, 95% CI 1.10 to 1.40, p<0.001) and low cholesterol (HR 1.59, 95% CI 1.17 to 2.01, p<0.001).Conclusion. In a population of patients with chronic stable coronary artery disease after myocardial revascularization with PCI, a decrease in the level of albumin, cholesterol, sodium, lymphocytes, hemoglobin, as well as an increase in the level of NT-proBNP were prognostic and statistically significant predictors of unfavorable prognosis in the form of all-cause mortality during 2 years of observation.